Are Smoking Habits Changing among Spanish Health Professionals? Results from the SUN Cohort 1999-2008 - M. Ruiz-Canela; M.A. Martínez-González; C. López-del Burgo; J. De Irala; J.J. Beunza; M. Bes-Rastrollo (SAGE Publishing, 2009)
Introduction Smoking by health professionals is a very negative habit not only for their own health, but also because it diminishes their capacity to influence their smoker patients to quit their habits. Objective The aim of this study was to assess the trend of the smoking prevalence, as well as the impact of the 2005 Spanish Smoking Act, among healthcare professionals. Methods Participants were asked about their smoking consumption in the baseline and the follow-up questionnaires in a Spanish dynamic prospective cohort of university graduates (the SUN Project) from 1999 to 2008. Non-conditional logistic regression models were fit to assess the relationship between type of profession and prevalence of smoking. Results The proportion of current smokers at the entrance into the cohort was 16.4% for physicians, 20.8% for pharmacists, 23.4% for nurses and 24% for other university graduates. The risk of being current smoker (adjusted OR [95% CI]) was lower in physicians (0.68 [0.61-0.76]) but not in pharmacists (0.94 [0.84-1.06]) or nurses (0.94 [0.84-1.05]) compared to other university graduates. All professional groups presented a statistically significant decline of smoking prevalence from 1999 to 2008. This decline might be at least partly due to the impact of the Spanish legislation on their smoking habits. Conclusion This study shows a decline in smoking prevalence among Spanish physicians. This decline has reached lower levels than what is current among other professionals and the general population. However, there is still a high number of smokers among health professionals, thus more efforts are needed to achieve lower levels of tobacco consumption.